Probiotics application in aquaculture: its potential effects, current status in China and future prospects - Rahayu, Silvana; Amoah, Kwaku; Huang, Yu; Cai, Jia; Wang, Bei; Shija, Vicent Michael; Jin, Xiao; Anokyewaa, Melody Abena; Jiang, Mouyan (Frontiers in Marine Science, 2024)
Today’s increasing demand for aquaculture production is accompanied by various challenges such as diseases, broodstock improvement, domestication, development of suitable pellets and feeding methods, hatchery technology, and water quality management. Thus, probiotic usage has been reported as the ideal alternative to antibiotics, other chemotherapeutics, and additional supplements to other alternative ingredients. The main beneficial roles of probiotics include the enhancement of disease and stress resistance, immunity, promotion of growth and reproduction, improvement of digestion, provide several nutrients, and enhancement of water microbial composition. To guarantee safety, the probiotics provided must be non-invasive and non-pathogenic. The use of probiotics in aquaculture, either directly or in combination with alternative materials such as plant protein diets, vitamins, microalgae, fermented products, and so on, has been shown to improve the health and growth of aquatic animals and offer significant benefits to the sustainability of the industry. There is advocacy for a systematic approach to conducting innovative research to unearth new putative strains, which is substantial in ensuring sustainable probiotic usage and, thus, can help in the continuous development of the aquaculture industry especially in China. Some examples of the probiotics found in China are mainly photosynthetic bacteria (PSB) which are autotroph bacteria capable of photosynthesis, antagonistic bacteria (Pseudoalteromonas sp., Flavobacterium sp., Alteromonas sp., Phaeobacter sp., Bacillus sp., etc.), bacteria that contribute nutrients and enzymes during digestion (lactic acid bacteria, yeasts, etc.), bacteria that improve water quality (nitrifying bacteria, denitrifying bacteria, etc.), Bdellovibrio, and other probiotics. This review also focuses on the potential use of probiotics in aquaculture, especially in China, and probiotics’ prospective future role.